Klimatsmart livsstil : Hur människor kan påverkas till att leva mer klimatsmart - Sandberg, Linnéa (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2018)
One of the greatest challenges of our time is the ongoing climate change. Research suggests that it is us humans that through our greenhouse gas emissions are the greatest cause of globalwarming and the problems that comes with it. To reduce the emissions of greenhouse gas and meet the international goals, it is necessary for individuals to make changes in their behavior. Some people care a lot about the climate and tries to do everything in their power to lower theirown impact, others want to do something but do not know what and some people does not care at all. The purpose of this study is to provide a deeper understanding of how to influence people to live in a more environmentally friendly way by identifying factors that determines environmentally friendly actions both positively and negatively. The study was conducted through a qualitative case study where the data collection was made through personal interviews with citizens in Luleå. The results of the study show that knowledge has a strong connection to individual behaviors. It is important to know that the environmental actions you take is of importance. Many people have the desire to do more than they do but are hindered by contextual factors like saving time. Except for the factors that was identified in the frame of reference the study also shows that there are other reasons for individuals to act in an environmentally friendly way: health, economy, ethics, frugality and care about future generations. By identifying these factors and get an explanation of how they impact individuals, the study can aid decision makers of a county with information that helps them adapt their conversion work to the citizens. The recommendations for counties are to provide citizens with clear information both regarding what goals they aim to reach as well as concrete actions to take in order to fulfil these, make it easier to choose environmentally friendly options, market the environmental benefits but also other reasons for certain behaviors since many people are more ...